Encouraging Humanism in the “Ponggol” Alms Distribution Procession of the Sacred Temple - Pramadhanti, Dhelinta Fitri; Aritonang, Firdaus; Saddhono, Kundharu; Islahuddin, Islahuddin (KARSA Journal of Social and Islamic Culture, 2022)
This research was conducted to find the value of humanism in the distribution of Ponggol in the earth alms tradition in Keramat Bumiayu Village, Brebes. The aim is that these values ​​can become a guide to life for the community, especially the younger generation, as preparation for becoming entirely social human beings and continuing to carry out the tradition of giving charity to the Earth. This research uses a qualitative method with a narrative approach and uses content analysis techniques from Milles and Huberman. The study obtained historical data regarding traditions and implementation, processions, and humanistic values ​​in the Ponggol distribution procession in the earth alms tradition at the Keramat Temple, Brebes Regency. In the ponggol distribution procession, there are human values, namely the value of cooperation, the value of being willing to sacrifice, the importance of caring for others, the value of helping each other, and the value of solidarity.